Biodegradation kinetics and microbial dynamics of toluene removal in a two-stage cell-biochar-filled biotrickling filter. (20th November 2019) - Lin, Chi-Wen; Tsai, Shen-Long; Lai, Chi-Yung; Liu, Shu-Hui; Wu, Chih-Hung
Abstract: The effectiveness of a series-connected biotrickling filter (SC-BTF) system in treating toluene vapors in a waste gas stream was evaluated. The SC-BTF was packed with cell-immobilized biochar beads and seeded mainly with Pseudomonas sp. YATO411 (a toluene degrader). The characteristics of packed beads and operating conditions, kinetics and microbial community of the SC-BTF in the removal of toluene were examined. The adsorption capacity of the cell-biochar beads was 16.03 kg toluene/m 3 -biochar beads. With a toluene loading of 100 g/m 3 ·h, the first biotrickling filter (BTF1 ) acted as a buffering matrix that reduced the cell toxicity of toluene to the microorganisms upon adsorbed toluene. The runoff toluene was completely degraded in the second biotrickling filter (BTF2 ). The maximum reaction rate (Vm ) of the cell-biochar bead-packed SC-BTF system (1134 g toluene/m 3 ·d) was 1.6 times that of another that was packed with Raschig rings. Microbial community analysis indicated that the YATO411 originally inoculated in the SC-BTF were the dominant strains under a moderate, starving, or shock loading of toluene. Graphical abstract: Image 1 Highlights: Biochar beads can be used as carriers of growing microbes to adsorb and degrade toluene. Beads can adsorb and self-desorb toluene after switching the inlet of biotrickling filter (BTF). Bamboo-derived biochar beads in BTF retain moisture and so can keep the entrapped microbes alive. Cell-biochar beads in BTF have a significantly higher reaction rate than that of Raschig rings.